Long-standing meningomyelocele can be a predictor of difficult airway and postoperative hypoventilation: challenge to the anaesthesiologist. (16th February 2016) - Sardar, Arijit; Khanna, Puneet; Singh, Abhishek; Sharma, Ankur
Abstract : A 15-year-old female patient presented with severe pain in the abdomen and obstructive uropathy. She underwent Yang-Monti ileovesicostomy under general anaesthesia. She is a known case of long-standing meningomyelocele (MMC) and presented with its potential complications such as difficult airway and restrictive lung disease. We describe the successful anaesthetic management of a case of anticipated difficult airway and postoperative hypoventilation as a sequel of kyphosis due to MMC. Her airway was secured with fibre optic-guided intubation in a semirecumbent position. Postoperative hypoventilation, hypercarbia and respiratory acidosis were managed conservatively, followed by staged weaning in the intensive care unit. Obstruction of the catheterisable continent channel of the neurogenic bladder itself may present with uropathy and urosepsis, which were also taken care of preoperatively.